2020
DOI: 10.1002/chem.202003360
|View full text |Cite
|
Sign up to set email alerts
|

The Application of HEXS and HERFD XANES for Accurate Structural Characterisation of Actinide Nanomaterials: The Case of ThO2

Abstract: The structuralc haracterisation of actinide nanoparticles (NPs) is of primary importance and hard to achieve, especially for non-homogeneous samples with NPs less than 3nm. By combining high-energyX-ray scattering (HEXS) and high-energy-resolution fluorescence-detected X-ray absorption near-edge structure (HERFD XANES) analysis,w eh ave characterised for the first time both the short-and mediumrange order of ThO 2 NPs obtained by chemicalp recipitation. By using this methodology,anovel insight into the structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 76 publications
(235 reference statements)
1
25
0
Order By: Relevance
“…One of the crucial aspects here is that the physical and chemical properties of the materials are changing as it comes to the nanoscale. HERFD methodology at the actinide M 4,5 edges has been successfully used in recent electronic structure investigations of the UO 2 66 , ThO 2 82 and PuO 2 61,63 nanoparticles (NPs). Authors experimentally traced the route of the Pu(VI) to PuO 2 NPs transformation as a two-step process 61 .…”
Section: Oxidation State Verificationmentioning
confidence: 99%
“…One of the crucial aspects here is that the physical and chemical properties of the materials are changing as it comes to the nanoscale. HERFD methodology at the actinide M 4,5 edges has been successfully used in recent electronic structure investigations of the UO 2 66 , ThO 2 82 and PuO 2 61,63 nanoparticles (NPs). Authors experimentally traced the route of the Pu(VI) to PuO 2 NPs transformation as a two-step process 61 .…”
Section: Oxidation State Verificationmentioning
confidence: 99%
“…9 A similar discrepancy between FDMNES calculations and data has been observed by the at the M 4 edge of ThO 2 . 22 Additionally, differences between the real local structure of U compared to the average structure represented by the crystal structure may also affect the calculated spectra. Indeed, EXAFS showed that for Sr 3 UO 6 two U−O distances are slightly shorter compared to the value from powder XRD results (2.04 Å instead of 2.07 Å), 25 and the intensity of the first peak in the XANES simulation increases if the local structure is modified according to EXAFS results.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Here we provide a brief review of two experimental techniques used to gleam information about sub-nanometer defects. Point defects in oxides such as UO2, CeO2, and ThO2 have been extensively characterized using light source techniques [322,332,333,334,335,336,337,338,339,340,341,342,343,344]. This field of study has recently been review by Lang, et al [345].…”
Section: Characterization Techniquesmentioning
confidence: 99%